View of the main temple structure - Temples of India Project Team (Jio Institute, 2024)
View of the main temple structure from the southwest. The garbhagriha, unlike the mandapa exterior, shows some decoration on its façade. The garbhagriha stands on base mouldings with jaali (checkered) windows and chaitya arches. It has a simple latina-type shikhara (spire) with niches topped by udgama pediments (pediments with interconnected chaitya dormers) which look like miniature shikaras. At the apex, an amalaka is placed topped by bijapuraka (citron fruit).